The Non-Muslim Minorities in the Islamic Community: Anthropological Study According to the Methodology of the Prophet Mohmmed (Peace be Upon Him) in the Communal Peace - RYAAD KANAN, QUSAY (Al-Adab Journal, 2020)
People differ in their nature because the difference is one of the origins of their creation and that the life we live is based on differences, contradiction and opposites. This is what God Almighty deposited in man and the wisdom of having made this human being the most honorable creatures and successors on earth. Since God sent His last messengers fourteen centuries ago, Islam considered the human rights of every human being of any race, of any religion and of any region, based on its philosophy of honoring man in terms of human being and rights prescribed in Islam. The rights of minorities in the Islamic community are confirmed rights in Islam, although unfortunately; there are those, opponents of Islam, who want to doubt that to make the issue of minorities an issue to stand in the face of the arbitration of Islamic law in Islamic societies of our time. In this study, we tried to find out the way the Muslims society deal with non-Muslim minorities and how these behaviors were based on the principles emphasized and inspired by the best examples of communal peace and cultural coexistence, Prophet Mohamed (Peace be Upon him,) in his actions and words with others.